The Language of Quotations in Hong Kong Chinese Newspapers - Lister, Anthony (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2015)
In Hong Kong standard written Chinese is Mandarin while Cantonese, which is the language of the vast majority of the territory’s population and is entirely acceptable when spoken, has very low status in its written form. This poses a problem for newspaper editors when quoting Cantonese speech. In the past, it was translated into Mandarin, but in recent years there has been an increasing use of Cantonese. This article examines the reporting of a speech in two different newspapers, the quality Ming Pao and the mass circulation Apple Daily, to study whether there was variation in the amount of Cantonese in the quotations. It was found that there was slightly less in Ming Pao than in Apple Daily, though not as much as might have been expected. There was also a greater use of quotation in Ming Pao Pao, which again was not expected based on earlier research. However, comparison with the actual words as recorded in a YouTube video revealed that both newspapers still reduced the amount of Cantonese.